2009
DOI: 10.1007/s10750-009-9880-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of an angiosperm-based classification system (BiPo) to Mediterranean coastal waters: using spatial analysis and data on metal contamination of plants in identifying sources of pressure

Abstract: The Biotic Index based on Posidonia oceanica (BiPo) is a classification system for evaluation of the ecological status in Mediterranean coastal waters, developed in accordance with the EU Water Framework requirements. The aim of this study is to verify the applicability and reliability of the BiPo index to different geographical areas of the north-western Mediterranean (France, Spain and Italy), to understand whether such a classification system may be applied more extensively, as so far it has only been appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…for phytoplankton (McQuatters-Gollop et al, 2009;HELCOM, 2010;Garmendia et al, 2011), for macroalgae Orfanidis et al, 2011;Sfriso & Facca 2011), for seagrasses (López y Royo et al, 2009), for benthos (Quintino et al, 2006;Chainho et al, 2008;Josefson et al, 2009;Borja et al, 2009a;Neto et al, 2010) and for fishes (Uriarte & Borja, 2009;Delpech et al, 2010;Cardoso et al, 2011).…”
Section: Identification Of Human Pressure-response Relationshipsmentioning
confidence: 99%
“…for phytoplankton (McQuatters-Gollop et al, 2009;HELCOM, 2010;Garmendia et al, 2011), for macroalgae Orfanidis et al, 2011;Sfriso & Facca 2011), for seagrasses (López y Royo et al, 2009), for benthos (Quintino et al, 2006;Chainho et al, 2008;Josefson et al, 2009;Borja et al, 2009a;Neto et al, 2010) and for fishes (Uriarte & Borja, 2009;Delpech et al, 2010;Cardoso et al, 2011).…”
Section: Identification Of Human Pressure-response Relationshipsmentioning
confidence: 99%
“…The present study has shown that a region as pristine as Corsica can be subject to significant anthropogenic pressures that influence local TE contamination levels. Indeed, in Corsica we find a wide range of types of pressure and environmental conditions representative of the western Mediterranean region (Lafabrie et al, 2008;Lopez y Royo et al, 2009). In Corsica, two stations (Ajaccio2 and Saint Florent2) are referenced as HCL sites with important concentrations in Zn, Fe, As, Al, and Cu.…”
Section: Introductionmentioning
confidence: 97%
“…The concentrations found indicate the type, nature, and exposure time of these contaminants to organisms in the study area . Based on this method, many classification tools have been developed to characterize the overall quality of water bodies and the health status of coastal ecosystems (Lopez y Royo et al, 2009;Richir and Gobert, 2014). It turns out that several species have specific criteria used to assess the contamination status of marine ecosystems which makes them good bioindicators (Zhou et al, 2008;Richir and Gobert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has yielded several lists of aquatic organisms divided into sensitive, indifferent and tolerant taxa. In some cases, this search for indicators has led to in-depth studies of a single species, applying different metrics combined into a multimetric index (Lopez y Royo et al, 2009). Information on taxa sensitivity or tolerance has been used in the assessment methods in various ways.…”
Section: Metricsmentioning
confidence: 99%
“…Kaiblinger et al, 2009;Ptacnik et al, 2009;Pall & Moser, 2009;Donahue et al, 2009;Lopez y Royo et al, 2009). Also, the intercalibration exercise has been carried out at the BQE level.…”
Section: Metricsmentioning
confidence: 99%